2013
DOI: 10.1371/journal.pone.0071639
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Blood Dendritic Cell Numbers and Functions after Aneurysmal Subarachnoid Hemorrhage

Abstract: Previous PresentationPortions of this study were presented at the Annual Congress of Société Française d’Anesthésie et de Réanimation in Paris, September 2012.BackgroundToll-like receptor (TLR) agonists are promising therapy for the prevention of nosocomial infections in critical ill patients. We aimed to analyze the TLR-reactivity of circulating dendritic cells (DC) as assessed by cytokine production after an ex vivo challenge with TLR agonists in aneurysmal subarachnoid hemorrhage (SAH) patients.Methods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…The number of circulating DCs was significantly lower in patients suffering from aneurysmal subarachnoid hemorrhage compared to that of healthy controls [50]. These DCs exhibited a remarkable anergic response to Toll-like receptor (TLR)3 and TLR4 stimulation, as evidenced by diminished production of TNF-α and IL-2, suggesting that aneurysmal subarachnoid hemorrhage-induced brain dysfunction compromised the function and viability of DCs [50]. Yilmaz and colleagues found that circulating DC precursors underwent transient decrease after acute stroke, which was correlated with the severity of brain injury [51].…”
Section: Dendritic Cellsmentioning
confidence: 79%
See 2 more Smart Citations
“…The number of circulating DCs was significantly lower in patients suffering from aneurysmal subarachnoid hemorrhage compared to that of healthy controls [50]. These DCs exhibited a remarkable anergic response to Toll-like receptor (TLR)3 and TLR4 stimulation, as evidenced by diminished production of TNF-α and IL-2, suggesting that aneurysmal subarachnoid hemorrhage-induced brain dysfunction compromised the function and viability of DCs [50]. Yilmaz and colleagues found that circulating DC precursors underwent transient decrease after acute stroke, which was correlated with the severity of brain injury [51].…”
Section: Dendritic Cellsmentioning
confidence: 79%
“…Monocytes/macrophages Decreasing the number of monocytes; polarization of M2 phenotype; increasing production of IL-10; reducing phagocytic capability [43], [44], [45] Neutrophils Impairment in ROS production; reduction of phagocytosis; shortening life-span as a result of spontaneous apoptosis [43,[46][47][48][49] Dendritic cells Decreasing number of circulating DCs; anergic response to TLR3 and TLR4 stimulations; incapable of priming effective cellular immune response; disturbed infiltration and aberrant phenotypic differentiation [50][51][52][53] T lymphocytes Reducing proportion of peripheral T cells; disturbing response to antigens; polarization of anti-inflammatory phenotypes; inducing imbalance between Tregs and proinflammatory phenotypes of T cells [54][55][56][57][58] sepsis, but they are rarely found in the normal brain [66]. Neutrophils accumulating in the central nervous system jeopardize brain cells by releasing inflammatory cytokines, increasing the activity of myeloperoxidase, and promoting oxidative damage [74].…”
Section: Types Of Immune Cells Changes In Function and Activity Refermentioning
confidence: 99%
See 1 more Smart Citation
“…After massive DAMP release, the early overwhelming inflammatory response can further leave an immunological scar that will be responsible for protracted immune alterations (IS) ( 84 ) and will worsen patient outcome. This IS decreases the capacity of monocytes to produce inflammatory cytokines after TLR stimulation ( 52 , 85 , 86 ) and APC to prime antigen on type 2 MHC molecules. Austermann et al highlighted that MRP linkage with TLRs induced phagocyte hyporesponsiveness to subsequent TLR agonist stimulation and was correlated with poor outcome ( 45 ).…”
Section: Novel Insightsmentioning
confidence: 99%
“…The frequency of myeloid dendritic cells producing TNF-α after application of TLR-3 agonist poly I:C significantly decreased in the SAH patients. In addition, myeloid dendritic cells producing administration of TLR-3 and 4 agonists decreased in the SAH patients compared to healthy subjects [137].…”
Section: The Role Of Toll-like Receptors In Subarrachnoid Hemorrhagementioning
confidence: 92%